Regulation of RNA granules by FMRP and implications for neurological diseases. (28th June 2020) - Lai, Austin; Valdez‐Sinon, Arielle N.; Bassell, Gary J.
Abstract: RNA granule formation, which can be regulated by RNA‐binding proteins (RBPs) such as fragile X mental retardation protein (FMRP), acts as a mechanism to control both the repression and subcellular localization of translation. Dysregulated assembly of RNA granules has been implicated in multiple neurological disorders, such as amyotrophic lateral sclerosis. Thus, it is crucial to understand the cellular pathways impinging upon granule assembly or disassembly. The goal of this review is to summarize recent advances in our understanding of the role of the RBP, FMRP, in translational repression underlying RNA granule dynamics, mRNA transport and localized. We summarize the known mechanisms of translational regulation by FMRP, the role of FMRP in RNA transport granules, fragile X granules and stress granules. Focusing on the emerging link between FMRP and stress granules, we propose a model for how hyperassembly and hypoassembly of RNA granules may contribute to neurological diseases. Abstract : Fragile X mental retardation protein (FMRP) is an RNA‐binding protein regulating diverse types of RNA granules to control translation and localization of mRNA. We summarize the known mechanisms of translational regulation by FMRP, and the role of FMRP in RNA transport granules, fragile X granules and stress granules. We discuss implications of our understanding on these topics in the context of neurodevelopmental and neurodegenerative diseases.